Crystallographic studies on 2-oxoglutarate dependent oxygenases - Aik, WS (2014)
The Fe(II) and 2-oxoglutarate dependent oxygenases (2OG oxygenases) catalyse a broad range of oxidative reactions in various organisms. 2OG oxygenases use 2OG and molecular oxygen to catalyse the oxidation of a variety of substrates including small molecules, fatty acids, nucleic acids and proteins. Several human 2OG oxygenases are implicated in diseases. The fat mass and obesity associated protein (FTO) is linked to obesity, whilst collagen prolyl-4-hydroxylases (CPHs), the procollagen lysyl hydroxylases (PLODs), and the hypoxia inducible factor hydroxylases (PHDs) are linked to cancer. Therefore, structure-based inhibition studies on FTO, CPH and related 2OG oxygenases are of significant therapeutic interest. The obesity-associated FTO is an mRNA N6-methyladenine (m6A) demethylase and a homologue of E. coli alkylated DNA repair protein (AlkB), a DNA repair enzyme that demethylates N1-methyladenine (m1A) and N3-methylcytosine (m3C) bases. Human AlkB homologue 5 (ALKBH5) has a similar substrate profile as FTO, i.e. ALKBH5 is another mRNA m6A demethylase, making it a target for structural and inhibition studies to improve inhibitor selectivity for FTO. The CPH and PLODs catalyse hydroxylation of collagen prolyl- and lysyl-residues; the resultant 4-hydroxyprolyl- and 4-hydroxylysyl-residues are important for the formation of the collagen triple helix and intermolecular crosslinks, respectively. Another 2OG oxygenase, the 2-oxoglutarate and iron-dependent oxygenase domain-containing protein 2 (OGFOD2), is related by sequence similarity to the PLODs but its biological role is unknown. This thesis describes crystallographic, biochemical and inhibition studies on five 2OG oxygenases: AlkB, FTO, ALKBH5, OGFOD2 and CPH. Three AlkB-inhibitor complexes were determined; taken together, these structures serve as proof-of-principle that the AlkB subfamily 2OG oxygenases are amenable to structure-based inhibition studies. Several classes of inhibitors of FTO were then identified and their binding modes were investigated through the determination of 7 crystal structures of FTO-inhibitor complexes. Subsequently, a crystal structure of ALKBH5 was determined, which provided insights into its substrate recognition mechanisms. The ALKBH5 structure also serves as a template for inhibitor design. Preliminary structural and biochemical data were also obtained for OGFOD2 and CPH. Overall, these results contribute to the development of a biophysical understanding of human 2OG oxygenases, and will help to enable the development of selective inhibitors of 2OG oxygenases involved in nucleic acid and collagen modifications.